Analisis Pengaruh Lingkungan Kerja, Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Karyawan - Nur Khoeriyah; Andi Yulianto; Azizah Indriyani; Indah Dewi Mulyani; Nur Aisyah (Journal of Economics and Management (JECMA), 2019)
Human Resources have a very important position in running the wheels of the organization, the success of an organization will not be separated from how competent its human resources are. Efforts to improve employee performance include paying attention to several factors, namely the work environment, work motivation and work discipline. In this study, researchers had the opportunity to carry out research on CV Dian Ayu Setiabudi. The purpose of this research is to explain the influence of the work environment, work motivation and work discipline on the performance of employees of CV Dian Ayu Setiabudi. This type of research is quantitative. The population and sample in this study were 40 employees of CV Dian Ayu Setiabudi. Determination of the sample in this study, using a simple random sampling method (random sampling). Data collection tools in this study were primary data, secondary data, questionnaires and interviews. The analytical method used is quantitative data analysis, descriptive analysis, multiple linear regression analysis, multiple correlation analysis and partial correlation analysis, with the help of SPSS 17. The results of this study indicate that the work environment, work motivation and work discipline have an effect simultaneously on employee performance such as which is shown by the significance level of F <α (0.000 <0.05) and Adjusted R-Square of 0.467. This means that the contribution of the work environment, work motivation and work discipline is 46.7% while the remaining 53.3%. Partially, the work environment has a significant effect on employee performance by 0.083, work motivation has a significant effect on employee performance by 0.001, and work discipline has a significant effect on employee performance by 0.968.